Analisis Manajemen Kurikulum Berbasis Total Quality Management dalam Organisasi Kurikulum dan Program Pengajaran - Muhammad Afiq; Slamet Untung; Wafda Sabilla; Risma Wati Agustina (CAHAYA: Journal of Research on Science Education, 2026)
This study aims to examine the implementation of curriculum management based on Total Quality Management (TQM) by reviewing curriculum organization, principles of curriculum development, and instructional program management. The research applied a qualitative approach using a library research method. Data sources were obtained from various references, including books, scientific journals, and articles related to the research topic. Data collection was conducted through documentation techniques, while data analysis employed descriptive qualitative methods. The findings indicate that systematically organized curriculum management can support effective learning achievement through proper arrangement of content scope, learning sequence, integration among subjects, balance of curriculum components, and appropriate time allocation. The principles of curriculum development, such as relevance, flexibility, continuity, efficiency, and effectiveness, serve as important foundations in designing curricula that align with students' needs and societal developments. Furthermore, the implementation of TQM in curriculum and instructional management contributes to improving educational quality through structured planning, continuous supervision, teacher professional development, and comprehensive evaluation. Therefore, the integration of TQM into curriculum management can become a strategic effort in creating quality, adaptive, and sustainable education systems.